2017
DOI: 10.1038/s41598-017-07376-5
|View full text |Cite
|
Sign up to set email alerts
|

Conditional knockdown of hyaluronidase 2 in articular cartilage stimulates osteoarthritic progression in a mice model

Abstract: The catabolism of hyaluronan in articular cartilage remains unclear. The aims of this study were to investigate the effects of hyaluronidase 2 (Hyal2) knockdown in articular cartilage on the development of osteoarthritis (OA) using genetic manipulated mice. Destabilization of the medial meniscus (DMM) model of Col2a promoter specific conditional Hyal2 knockout (Hyal −/−) mice was established and examined. Age related and DMM induced alterations of articular cartilage of knee joint were evaluated with modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Hyals can also cleave bigger size hyaluronic acid to alter the organization and stability of aggrecan. This idea is supported by the observation that Hyal2 deficient mice show cartilage development disorders and osteoarthritic like cartilage degeneration [30]. We demonstrated that Hyal2 and Hyal3 protein expression reduced on days of chondrogenic differentiation, while Hyal4 was elevated and Hyal1 was not altered on these days.…”
Section: Discussionsupporting
confidence: 72%
“…Hyals can also cleave bigger size hyaluronic acid to alter the organization and stability of aggrecan. This idea is supported by the observation that Hyal2 deficient mice show cartilage development disorders and osteoarthritic like cartilage degeneration [30]. We demonstrated that Hyal2 and Hyal3 protein expression reduced on days of chondrogenic differentiation, while Hyal4 was elevated and Hyal1 was not altered on these days.…”
Section: Discussionsupporting
confidence: 72%
“…The camera used was DP71 (Olympus). Like in previous reports, the number of positive cells in each group was calculated as described below, and the differences subjected to statistical analysis [ 33 ]. The number of positively stained cells was counted in articular cartilage.…”
Section: Methodsmentioning
confidence: 99%
“…HYAL1 is primarily an intracellular, low pH, lysosomal hyaluronidase. Recent studies using a conditional (Col2a-Cre) Hyal2 −/− reported increases in HA within the PCM, increased overall HA and increased HA size [46]. HYAL2 is considered a cell surface [47], endosomal [48] and lysosomal hyaluronidase [49,50].…”
Section: Ha Turnover Within the Pcmmentioning
confidence: 99%
“…HYAL2 is considered a cell surface [47], endosomal [48] and lysosomal hyaluronidase [49,50]. In fact, many of the hyaluronidases and receptors that have been considered as critical participants in HA turnover including: HYAL1, HYAL2, HYAL3 [46,[51][52][53][54], CD44 [23,24,[55][56][57], PH-20 [58], KIAA [59] and TMEM2 [60] all are associated with the chondrocytes and PCM. Lastly, Fosang et al using confocal microscopy, observed the accumulation of intracellular G1-ITEGE in situ within cartilage chondrocytes of porcine articular cartilage [61].…”
Section: Ha Turnover Within the Pcmmentioning
confidence: 99%